Synthesis and Characterization of Theranostic Poly(HPMA)-c(RGDyK)-DOTA-Cu Copolymer Targeting Tumor Angiogenesis: Tumor Localization Visualized by Positron Emission Tomography - Jianchao Yuan; Haiyuan Zhang; Harpreet Kaur; David Oupicky; Fangyu Peng (Molecular Imaging)
Poly(HPMA)-c(RGDyK)-DOTA- 64 Cu copolymers were synthesized and characterized for tumor localization in vivo as a theranostic scaffold for cancer imaging and anticancer drug delivery targeting tumor angiogenesis. Tumor localization of the poly(HPMA)-c(RGDyK)-DOTA- 64 Cu copolymers was visualized in mice bearing human prostate cancer xenografts by positron emission tomography (PET) using a microPET scanner. PET quantitative analysis demonstrated that tumor 64 Cu radioactivity (2.75 ± 0.34 %ID/g) in tumor-bearing mice 3 hours following intravenous injection of the poly(HPMA)-c(RGDyK)-DOTA- 64 Cu copolymers was significantly higher than the tumor 64 Cu radioactivity (1.29 ± 0.26 %ID/g) in tumor-bearing mice injected with the nontargeted poly(HPMA)-DOTA- 64 Cu copolymers ( p = .004). The poly(HPMA)-c(RGDyK)-DOTA- 64 Cu copolymers hold potential as a theranostic scaffold for cancer imaging and radiochemotherapy of prostate cancer targeting tumor angiogenesis by noninvasive tracking with PET.